Penerapan Metode Targhib dan Tarhib dalam Pembelajaran di Madrasah Aliyah Negeri (MAN) 2 Medan - Syahrul, Nursyahrul Ritonga; Ramadhani, Muhammad Luthfie (Jurnal Kajian Ilmu Pendidikan (JKIP), 2025)
Educating children with the method of giving rewards and punishments is often looked down upon by educators, because it is very common. So that the existing provisions and rules are forgotten and many do not realize that things that are considered trivial have rules. In fact, mistakes when applying this educational method can have fatal consequences, namely damaging the child’s personality that was previously well formed. No educator wants punishment to be used in education unless forced. Rewards or praise are much more important than punishment. In the world of Islamic education, this method is called the Targhib and Tarhib method. This method is a method that is commonly used in the teaching and learning process. Just like in the use of the targhib and tarhib approach to students in a preventive or repressive manner, with the hope that through giving rewards and applying these punishments, it can prevent various violations of the rules and can provide strong motivation that arises entirely from fear of the threat of punishment. With this method, it is hoped that students can be motivated to carry out progressive actions. This study aims to describe the application of the targhib and tarhib methods in learning at MAN 2 Medan.